A STUDY ON INTER-STATE DISPARITIES IN PUBLIC HEALTH EXPENDITURE AND ITS EFFECTIVENESS ON HEALTH STATUS IN INDIA - Ganesan, L.; Veena, R. Senthamizh (International Journal of Research -GRANTHAALAYAH, 2018)
Public health services play an important role in the health status of the people and Health Expenditure by the Government occupies crucial part in influencing the health outcome in the country. The healthcare finances are influenced by the respective State’s budgetary allocation which leads to inter-state disparity in health services and health status in India. This has implications on providing Universal Health Coverage, which aims at ensuring equitable health services to people at all levels in the country (National Health Portal, GoI). The researcher has selected 15 major states based on the level of population (which accounts for about 90 percent of the total population in India) to analyse the inter-state disparities in health sector. Alongside, this study focuses on the performance of public health sector of the selected states through a comparative analysis of various parameters depicting health expenditure, availability of health services, their utilization and health outcomes. With vast variation in the availability, affordability and utilisation of health services across different states, it is found that the economic conditions, health finance, infrastructure and effectiveness of health services at the state level have direct bearing on the health status of the people in the respective states. Therefore, it is essential to take necessary corrective measures that target the disparity, to achieve better and equitable health services for all, leading to Universal Health Coverage which is the real inclusiveness.